Fueling Success: Unleashing the Power of Motivation, Nurturing Work Environments, and Cultivating Organizational Culture for Peak Job Satisfaction and Performance - Putra, Rizaldi; Kudri, Wan Muhamad (First Ciera Publisher, 2024)
This study seeks to assess, analyze, and quantify the influence of Motivation, Work Environment, and Organizational Culture on both Job Satisfaction and Teacher Performance in State Elementary Schools within Cluster VI of Bengkalis District. The research encompasses 119 teachers, representing the entire population, and employs a census technique. The methodology involves descriptive analysis and hypothesis testing, utilizing Path analysis through SPSS 21 and SmartPLS programs. The findings from hypothesis testing reveal a positive and significant correlation between motivation and job satisfaction. However, the impact of work motivation on performance is positive but not statistically significant. Similarly, the positive relationship between Work Environment and Job Satisfaction is identified, but it lacks a significant impact. The positive association between Work Environment and Performance is observed, yet without a significant impact. Organizational Culture demonstrates a positive link with Job Satisfaction, though lacking a significant impact. However, it positively correlates with Performance and has a significant impact. Interestingly, Job Satisfaction is positively related to performance, yet it does not significantly influence the performance of civil servant teachers in SD Cluster I, Bengkalis District.